(untitled) - Schaefer, Richard T. (Boston, MA, 2008)
The book was very useful for my class, a bit repetitive at times but it helped me get an A in Sociology : D. Also I was very impressed with the seller, he shipped it quickly and i received it quickly. The book came in the exact condition it was described as.
Keywords: Sociology,Cultural relations,Social stratification,Xã hội học,Quan hệ văn hóa,Tầng lớp xã hội